The influence of some factors on the reproduction and growth of Saccharomyces cerevisiae MS42 - Quyên, Nguyễn Văn; Thảo, Nguyễn Quang; Anh, Nguyễn Thảo; Đạt, Nguyễn Thành (Vietnam Journal of Biotechnology, 2016)
Research on the growth of yeast is a critical requirement, occupying an important role in the technology of alcohol production. In reality, there are many factors affecting on the reproductive process and the growtht of yeast such as: temperature, pH, dissolved oxygen content, sugar content, nutrients, etc... The quantity and quality of yeast decide the quality on the wine products. When the amount of yeast is abundant, the fermentation speed is faster, which is an important factor in preventing infection from harmful microorganisms during fermentation. The study on influences affecting the growth of yeast is necessary to ensure the main aim of the propagation which is to create good quality breeding populations of yeast in a short time period. Furthermore, this has important implications for the fermentation process to create good products. Besides, increasing the speed and the number of yeast cells in practice, efficient, inexpensive materials used, as well as a common key element in the production process also bring high economic efficiency. In this study, basic factors affecting the growth of the species Saccharomyces cerevisiae MS42 we determined. Optimal conditions and compositions of the medium for breeding are shown in following: sugar content is 80 g/l: pH = 5.0; temperature from 28oC, the amount of dissolved oxygen from the initial is 7.0 mg/l, after 24 hours of incubation (since followed the same), the number of yeast cells has reached the maximum (219.5 ± 3.0 million cells/ml) and budding cell ratio (approximately 70 - 72%).